THE EFFECTIVENESS OF USING WORDWALLS TO IMPROVE STUDENTS' UNDERSTANDING OF INDONESIAN CULTURAL DIVERSITY MATERIAL - Ani Setianingsih; Anik Widiastuti; Agustina Tri Wijayanti; Suranto Suranto (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2026)
This study aims to investigate the effectiveness of the Wordwall interac-tive learning media in improving fifth-grade students' understanding of the topic "Cultural Diversity in Indonesia" at SDN Karanggeneng 1. The research employs a quantitative approach using a one-group pretest-posttest design. A total of 15 students were selected through total sam-pling as the study sample. Data collection was conducted using pretest and posttest instruments to measure students' cognitive understanding before and after the intervention. The data were analyzed using descrip-tive statistics and the Paired Sample t-Test with SPSS 21. The results show a significant increase in students' scores, from a pretest average of 77.07 to a posttest average of 95.03. The Paired Sample t-Test results indicated a Sig. (2-tailed) value of 0.000 < 0.05 and a t-count value of 21.017 > t-table 2.145, confirming a statistically significant difference. Moreover, the reduced standard deviation from 2.89 to 1.99 shows more consistent and evenly distributed learning outcomes. These find-ings demonstrate that Wordwall significantly enhances students' learn-ing and engagement through interactive quizzes, games, and puzzles. Wordwall supports student-centered and visual learning styles aligned with digital-native learners. The study concludes that Wordwall is not only effective in improving learning outcomes but also fosters an en-gaging and active classroom atmosphere. This research contributes to the development of innovative learning strategies and suggests the broad application of interactive digital media to strengthen students' cultural understanding and appreciation of national diversity. Future research is recommended to explore other cognitive, affective, and psy-chomotor aspects with a larger and more varied sample.